Optimizing rearing duration to improve broiler production indices in conventional open sided and tunnel ventilated closed sheds during summer season (Indian Journal of Animal Production and Management, 2018)
Present study was conducted to compare the effect of the rearing duration, housing type and stocking  density on resource use efficiency of broiler production during summer. A total of 984 day old broiler chicks  were subjected to different treatments i.e. T0 (birds with floor space,1.0/ft2/ bird in open sided conventional  broiler house (OSCBH) as control, while different treatments in tunnel ventilated environment control  broiler house (ECBH) were T1, T2, T3, T4 and T5 with floor space of 1.0, 0.9, 0.8, 0.7and 0.6 ft2 per bird,  respectively. Growth performance and economic returns in all treatments in both types of housing decreased  after 5th week of age. After 5th week, body weight (1624.19vs1386.01 g),feed intake(1016.53 vs 924.53  g), FCR(4.37vs3.94), PER(1.22vs 1.16), EER(14.13vs 12.59) and economic return was significantly(P≤  0.05) better in ECBH (T2) than OSCBH (T0) even at 10% higher stocking density.
Keywords: Broiler; Growth performance and economics; Heat stress; Tunnel ventilation